2018
DOI: 10.1007/s12975-018-0615-1
|View full text |Cite
|
Sign up to set email alerts
|

Focal Ischaemic Infarcts Expand Faster in Cerebellar Cortex than Cerebral Cortex in a Mouse Photothrombotic Stroke Model

Abstract: It is generally accepted that the cerebellum is particularly vulnerable to ischaemic injury, and this may contribute to the high mortality arising from posterior circulation strokes. However, this has not been systematically examined in an animal model. This study compared the development and resolution of matched photothrombotic microvascular infarcts in the cerebellar and cerebral cortices in adult 129/SvEv mice of both sexes. The photothrombotic lesions were made using tail vein injection of Rose Bengal wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 57 publications
1
11
0
1
Order By: Relevance
“…This revealed a high capacity of microglia to activate after a disruption in tissue homeostasis. Recently, a series of studies revealed the presence of activated microglia in the acute phase [ 22 ], sub-acute phase [ 23 ], and chronic phase [ 24 ] of IS. The aforementioned morphology changes are associated with different activated microglia functions.…”
Section: Microgliamentioning
confidence: 99%
“…This revealed a high capacity of microglia to activate after a disruption in tissue homeostasis. Recently, a series of studies revealed the presence of activated microglia in the acute phase [ 22 ], sub-acute phase [ 23 ], and chronic phase [ 24 ] of IS. The aforementioned morphology changes are associated with different activated microglia functions.…”
Section: Microgliamentioning
confidence: 99%
“…Inflammation is a universal response to stroke that has been well described clinically and in animal models as a target for therapeutic intervention (Jayaraj et al, 2019;Shi et al, 2019). The vast majority of these studies have limited their analyses to the acute and subacute period after injury, that is days or weeks after large strokes (Gorlamandala et al, 2018;Morioka et al, 1993;Price et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Along with conventional approaches to induce ischemic stroke, thromboembolic ischemia is an alternative modality used via the injection of thrombin directly into the middle cerebral artery [6]. In recent decades, the acute photothrombotic (PT) stroke model has been developed for the focal ischemic changes by local infusion photo-sensitive dye into the venous circulation [7,8]. Initially, Rosenblum and El-Sabban in 1977 introduced the PT model which later improved by Watson in 1985 [9].…”
Section: Introductionmentioning
confidence: 99%